Visitor segmentation in a mountain national park: the case of Karkonosze National Park in Poland - Mateusz Rogowski (Studia Periegetica, 2021)
As the number of people visiting national parks in Poland is constantly growing, it is important to recognise their varying motivations and preferences. This is particularly important in the most popular national parks, such as the National Park in the Karkonosze Mountains (KNP). KNP is visited by two millions tourists annually, which makes it the second most popular national park in Poland. The aim of study was to classify visitors of the national park in terms of their motivation to visit. Three main categories of visitors were identified: leisure seekers, nature lovers and active tourists. The category of leisure seekers was the largest and most diverse with respect to their preferences. Nature lovers knew a lot about the park, especially as regards its geodiversity and its fauna and flora. The number of active visitors keeps growing every year. Active tourism, especially in the KPN, requires advanced equipment and good physical fitness. The findings of the study tourism trends in mountain national parks and can provide insights for its management. The article ends with some predictions regarding future trends and changes in the classification of KPN visitors after the pandemic.